Ecological classification of natural plants east of Wasit governorate - Hassoun, Nour; Kanaan, Hossam (Al-Adab Journal, 2023)
This study dealt with the topic of environmental classification of natural plants in the east of Wasit governorate, as there are many types of classifications of natural plants, and in our research, the environmental classification of natural plants was highlighted, as the plants were linked to the geomorphological phenomena of the surface of the region, and the plants in the region were classified on six plant environmental types, namely (nesting Hills environment, Sabkhat environment, grassy steppe environment, river banks environment– woody plants, river banks environment prominent plants(